Psychological, mobility, and satisfaction variables mediate the relationship between baseline back pain intensity and long-term outcomes in individuals who underwent lumbar spine surgery. (October 2021) - Garcia, Alessandra N.; Cook, Chad E.; Gottfried, Oren
Abstract: Background: In patients who receive spine surgery, pain is relational to disability and quality of life, but exactly how this influence is mediated is not fully understood. Mediation analyses allow an understanding of a known relationship by exploring the underlying mechanism or processes by which one variable influences another. Objectives: To determine the mediating influence of psychological, mobility, and satisfaction variables on the relationship between preoperative back pain intensity and 12-month disability and quality of life in individuals who underwent lumbar spine surgery. Design: This mediation analysis study used data from the Quality Outcomes Database (QOD) Lumbar Spine Surgical Registry. Methods: There were included individuals who received lumbar spine surgery for degenerative spine conditions. The exposure variable was preoperative back pain intensity. Mediator variables were depression/anxiety, mobility, and satisfaction. Outcomes included disability and quality of life. Separate multiple mediator models were conducted using the Hayes PROCESS, Model 4 with bias-corrected bootstrapping (5000 samples) to predict disability and quality of life. Results: 26, 130 individuals (n = 13, 740 males, mean age 60.2 [SD = 13.8) were included. We observed a significant indirect effect through the mediators (anxiety/depression, mobility and satisfaction), for both disability ( b  = 0.31, 95%CI = 0.26, 0.35) and quality of life ( b  = −0.44, 95%CI = −0.48, −0.41). Conclusion: Our study suggests that the relationship between preoperative back pain intensity (exposure) and long-term disability and quality of life (outcomes) is partially mediated by anxiety/depression, mobility, and patient satisfaction in individuals who received lumbar spine surgery. Highlights: A large national database was used to test the mediating influence of three variables. The mediator variables included anxiety/depression, mobility and satisfaction. The mediators explained 31% of the relationship between back pain and disability. The mediators explained 50% of the relationship between back pain and quality of life.